Prevalance and associated factors of diabetic foot at risk among type 2 diabetes mellitus patients attending primary health clinics in Kuantan - Abdul Hadi, Azwanis; Azmi, Nurul Husna; Md Aris, Mohd Aznan; Che Ahmad, Aminudin; Nasreen, Hashima E (2019)
Background: Foot complications are considered to be a serious consequence of diabetes mellitus, posing a major medical and economic threat. Identifying the extent of this problem and its risk factors will enable health providers to set up a better prevention programs. Objectives: This study aims to assess the prevalence of diabetic foot at risk and its associated factors among the type 2 diabetes mellitus patients’ attending primary health clinics in Kuantan. Methods: This was a cross-sectional study conducted at four primary health clinics in Kuantan involving 450 study participants who were selected by using universal sampling method. Level of awareness and practice toward diabetic foot care was assessed using validated self-administered questionnaire. Foot examination carried out and foot at risk was classified based on Kings’ Classification. Multiple logistic regressions were performed to identify the risk factors for diabetic foot at risk. Results: The prevalence of diabetic foot at risk was 31.3% (95% CI: 0.27, 0.36) according to Kings Classification (stage 2). Mean age of respondents involved was 56.36 (SD±10.9) years. Multivariate logistic regression analysis identified age (OR 1.04, 95%CI: 1.01-1.06), smoker (OR .911, 95%CI: 1.96-8.63) and duration of diabetes more than 10 years (OR1.77, 95%CI: 1.05-2.98) were risk factors for diabetic foot at risk. However, respondents with good practice score (OR 0.87, 95%CI: 0.774-0.980) have lesser risk of developing diabetic foot at risk. However, level of awareness, race, gender, education level and diabetic control did not show any significant association with diabetic foot at risk. Conclusion: Based on the result, it can be concluded that the screening for diabetic foot at risk is vital for early detection and intervention to prevent serious complication. A sustainable patient education and compliance towards practice of foot care at primary care level should be emphasized more to ensure good foot care practice implementation.